Trust, knowledge sharing, and innovative work behavior: empirical evidence from Poland - Kmieciak, Roman (European journal of innovation management, 2021)
PurposeThe purpose of this paper is to assess the effects of two types of trust (vertical and horizontal trust) on knowledge sharing (knowledge donating and knowledge collecting) and the impact of knowledge sharing on innovative work behavior (idea generation and idea realization). The study also explores the mediating role of knowledge sharing.Design/methodology/approachPartial least squares path modeling and data collected from 252 participants at one large Polish capital group were used to test the research hypotheses.FindingsThe results showed that both vertical trust and horizontal trust are positively related to knowledge donating and knowledge collecting. Contrary to knowledge collecting, knowledge donating is significantly related to idea generation, which is highly correlated with idea realization. There is no direct relation between knowledge sharing behavior and idea realization. Knowledge donating mediates the relationship between vertical trust and idea generation.Research limitations/implicationsSelf-reports and the cross-sectional nature of the data collection are the main limitations of this study.Practical implicationsThe results allow managers to better understand what factors and processes contribute to greater employee innovativeness.Originality/valueTo the best of the author's knowledge, the study is the first to examine the relationships among vertical trust, horizontal trust, knowledge donating, knowledge collecting, idea generation and idea realization in an integrated way. This paper answered the questions (1) which type of trust is more important for knowledge sharing, and (2) which type of knowledge sharing behavior is more important for innovative work behavior. This paper investigated whether differences in the strength of relationships between constructs are significant.